Releasing the restraints of Vγ9Vδ2 T-cells in cancer immunotherapy - Ridgley, Laura A.; Caron, Jonathan; Dalgleish, Angus; Bodman-Smith, Mark (Frontiers in Immunology, 2023)
Objectives: Vγ9Vδ2 T-cells are a subset of T-cells with a crucial role in immunosurveillance which can be activated and expanded by multiple means to stimulate effector responses. Little is known about the expression of checkpoint molecules on this cell population and whether the ligation of these molecules can regulate their activity. The aim of this study was to assess the expression of both activatory and inhibitory receptors on Vγ9Vδ2 T-cells to assess potential avenues of regulation to target with immunotherapy. Methods: Expression of various activatory and inhibitory receptors was assessed on Vγ9Vδ2 T-cells by flow cytometry following activation and expansion using zoledronic acid (ZA) and Bacillus Calmette-Guérin (BCG). Expression of these markers and production of effector molecules was also examined following co-culture with various tumour cell targets. The effect of immune checkpoint blockade on Vγ9Vδ2 T-cells was also explored. Results: Vγ9Vδ2 T-cells expressed high levels of activatory markers both at baseline and following stimulation. Vγ9Vδ2 T-cells expressed variable levels of inhibitory checkpoint receptors with many being upregulated following stimulation. Expression of these markers is further modulated upon co-culture with tumour cells with changes reflecting activation and effector functions. Despite their high expression of inhibitory receptors when cultured with tumour cells expressing cognate ligands there was no effect on Vδ2+ T-cell cytotoxic capacity or cytokine production with immune checkpoint blockade. Conclusions: Our work suggests the expression of checkpoint receptors present on Vγ9Vδ2 T-cells which may provide a mechanism with the potential to be utilised by tumour cells to subvert Vγ9Vδ2 T-cell cytotoxicity. This work suggests important candidates for blockade by ICI therapy in order to increase the successful use of Vγ9Vδ2 T-cells in immunotherapy.